Establishing a Living Donor Kidney Transplant Program in a Sub-Saharan African Country: Living Kidney Donor Characteristics and Outcomes in Ethiopia. (July 2018) - Gelan, Engida; Ahmed, Momina; Punch, Jeffery D.; Bekele, Mahteme; Berehe, Teklebirhan; Tadese, Mekdim; Woodside, Kenneth; Leitchman, Alan; Tedela, Faski; Abate, Mersema; Assefa, Seyum; Abebe, Zerihun; et al.
Abstract : Background: Renal replacement therapy utilizing dialysis or kidney transplantation is the standard of care for patients with end stage renal disease, with transplantation as the preferred approach. Until a few years ago, transplantation was unavailable, and almost unthinkable, in Ethiopia. However, with the collaboration of the Ethiopian Ministry of Health and the University of Michigan, we have established a successful kidney transplant program in the Ethiopian capital. We sought to describe the socio-demographic characteristics and surgical outcomes of living kidney donors at our nascent program. Methods: We retrospectively analyzed all living kidney donors who underwent donor nephrectomy at the Ethiopian Ministry of Health National Kidney Transplant Center, located at St. Paul's Hospital Millennium Medical College in Addis Ababa, between September 2015 to August 2017. All donors were evaluated by nephrologists, surgeons, and a psychiatrist. The psychiatrist also served the role of independent donor advocate. Results: A total of 52 living donor nephrectomies were performed in the first two years of the clinical program. Of these donors, 28 (53.8 %) were female. Donor age ranged from 21to 66 with a mean of 32.8 years. Mostly donors were siblings (44.2%) or parents (13.5%) of the recipient. The first 42 donors received hand-assisted laparoscopic donor nephrectomies (HALDN), with a conversion rate of 6.7 %. More recently, a mini-incision ( 10 cm) open donor nephrectomy technique has been utilized. All nephrectomies were left-sided, with 48 (92.3%) of the donors having single renal artery anatomy. The mean operative time and estimated blood loss were 159 minutes and 160 ml, respectively, for HALDN, and 126 minutes and 220 ml, , respectively, for the open approach. Only 3 patients had early post-operative complications, with one patient suffering an unexplained SBO, one having superficial surgical site infection and one suffering from Atelectasis. No donors died or demonstrated renal failure during the study period. Conclusions: The donor evaluation process and surgical approach are similar to transplant centers in other countries with well-established transplant systems, and include the use of an independent donor advocate. For our growing Ethiopian transplant program, outcomes for living kidney donors are excellent over the last 2 years, and are comparable to established international transplant standards. Key words – transplant, living kidney donor, outcome